`3x+11` 
`x-2``{:)``3x^2+5x-8` 
  `3x^2-6x`We multiply `(x-2)` by `3x =` ` 3x^2-6x`, giving `3x^2` as the first term.
  `11x-8``5x-(-6x)` ` = 5x+6x` `=11x`. Then bring down the `-8`.
  `11x-22`Multiply `(x-2)` by `11=` `11x-22`.
  `14``-8-(-22) ` `= 14`. This is the remainder.

Thus, we can conclude that:

3x2 + 5x − 8 = (x − 2)(3x + 11) + 14

where the quotient `q(x) = 3x + 11` and the remainder `R = 14`.

We can also write our answer as:

`(3x^2+5x-8)-:(x-2)` `=(3x+11)+14/(x-2`

Easy to understand math videos:
MathTutorDVD.com